Implementasi Manajemen Mutu Terpadu Dalam Rangka Meningkatkan Prestasi Belajar Bagi Siswa SMK TRI’S Maros - Andi Mappincara; Andi Nurochmah (Seminar Nasional LP2M UNM, 2021)
Abstract. The problem in this research is the application of integrated quality manajemen in order to improve student achievement at SMK TRI’S Maros. The method used in this research is naturalistic qualitative, Collecting data through observation, interviews and documentation. Subjects in this study : prinscipals, teachers, employees and students. The validity of the data used is triangulation, interactive analysis through data collection activities. Data reduction, data presentation and conclusion drawing. The results of this study indicate that:1. The quality of services provided to student at SMK TRI’S Maros has met good service standards, in this case the facilities and infrastructure are adequate,.2. In the learning process has show the quality of good human resources and has S1 and S2 qualifications in accordance whit their expertise. 3. SMK TRI’S Maros seen from the quality of the environment is good, it is proven that the geographical location of the school is strategic because the school is on the axis between Makassar and Maros so that it is easy for students to reach. Especially for those who do not have a vehicle.4. Interms of quality, the learning process is considered good because it is supported by high teacher responsibility. This is evidenced by the realization of a conducive learning plan with the readiness of lesson plans for each subject and the teachers’s learning process using mathematics geography learning for each learning material as well as proper evaluation of learning for each.Keywords: Integrated Quality Management, Implementation leaorning, Student Achievement